Characteristics and prognosis of Herpesviridae-related pneumonia in critically ill burn patients. Issue 5 (August 2022) - Dépret, François; Riaud, Charline; Rouaux, Jil; Chaussard, Maïté; Fratani, Alexandre; Cupaciu, Alexandru; Coutrot, Maxime; Guillemet, Lucie; Oueslati, Haikel; Benyamina, Mourad; Mebazaa, Alexandre; Lafaurie, Matthieu; et al.
Highlights: HSV reactivation occurred in more than 50% of ventilated severely burn patients. Sex, SOFA score and smoke inhalation were associated with HSV reactivation. Neither HSV reactivation nor treatment were associated with prognosis. Abstract: Background: The aim of this study was to describe the prevalence, characteristics and outcome of critically burn patients with pulmonary HSV reactivation. Methods: Retrospective, single-center cohort study in a burn critical care unit in a tertiary center, including all consecutive severely burn patients with bronchoalveolar lavage performed for pneumoniae suspicion and screened for HSV from January 2013 and April 2017. We used logistic regression to identify factors associated with HSV reactivation and outcomes. Results: 94 patients were included, mean age was 51 (39−64) years; median total body surface area burned was 36 (25–54)% and ICU mortality 38%. Fifty-five patients (59%) had pulmonary HSV reactivation and 30 (55%) were treated with acyclovir. Patients with HSV reactivation were more severely ill with higher SOFA score at admission compared to patient without HSV reactivation (6 [3–8] vs. 2 [1–4], p < 0.0001 respectively). In multivariate analysis, sex, SOFA score at admission and smoke inhalation were significantly associated with HSV reactivation. Only septic shock was associated with 90-day mortality when HSV reactivation was not. Conclusions: Pulmonary HSV reactivation is frequent among severely ill burn patients. Initial severity and smoke inhalation are risk factors. Antiviral treatment was not associated with outcome.